How effective are unemployment benefit sanctions? Looking beyond unemployment exit - Patrick Arni; Rafael Lalive; Jan C. van Ours (Institute for the Study of Labor (IZA), 2009)
This paper provides a comprehensive evaluation of benefit sanctions, i.e. temporary reductions in unemployment benefits as punishment for noncompliance with eligibility requirements. In addition to the effects on unemployment durations, we evaluate the effects on post-unemployment employment stability, on exits from the labor market and on earnings. In our analysis we use a rich set of Swiss register data which allow us to distinguish between ex ante effects, the effects of warnings and the effects of enforcement of benefit sanctions. Adopting a multivariate mixed proportional hazard approach to address selectivity, we find that both warnings and enforcement increase the job finding rate and the exit rate out of the labor force. Warnings do not affect subsequent employment stability but do reduce post-unemployment earnings. Actual benefit reductions lower the quality of post-unemployment jobs both in terms of job duration as well as in terms of earnings. The net effect of a benefit sanction on post-unemployment income is negative. Over a period of two years after leaving unemployment workers who got a benefit sanction imposed face a net income loss equivalent to 30 days of full pay due to the ex post effect. In addition to that, stricter monitoring may reduce net earnings by up to 4 days of pay for every unemployed worker due to the ex ante effect.
Keywords: J64; J65; J68; 330; Benefit sanctions; earnings effects; unemployment duration; competing-risk duration models; Arbeitslosigkeit; Arbeitslosenversicherung; Arbeitsuche; Ökonomischer Anreiz; Statistische Bestandsanalyse; Schweiz